Recommendations for education with patient simulation in higher education (Research, Society and Development, 2022)
Objective: To present recommendations for the use of simulated patients in higher education. Methodology: This is a Scoping review according to The Joanna Brigs Institute, carried out in the Latin American Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online databases, and in the Scientific Electronic Library Online electronic library through the online platform. CAPES journals. Original articles were included, and review, reflection or articles that did not meet the objective were excluded. The data search and selection process was described in the Preferred Reporting Items for Systematic Reviews and Meta Analyzes flow. Result: 557 studies were identified, of these six articles met the study criteria, two national and four international, published between 2010 and 2019. The recommendations refer to (1) the characterization of the simulated patient and (2) the simulation script and simulated patient training. Conclusions: Therefore, educational institutions must adopt them in the teaching-learning process.